GURU PENGGERAK AND NON-PENGGERAK TEACHER PERCEPTION ON IMPLEMENTATION OF PROBLEM BASED LEARNING IN ENGLISH LANGUAGE TEACHING - Salim, Agus; Bte Abdul, Nurdevi; Andi Asri Jumiaty (Journal of Language Testing and Assessment, 2024)
This research aimed at finding out Guru Penggerak and non-penggerak teacher perception on the implementation of problem-based learning in English language teaching. The method of this research was case study. Data of the research were collected through observation and interview. This research was conducted at SMA Negeri 8 Makassar with two teachers as a subject. The subject was divided into Guru Penggerak and non-penggerak teacher. The techniques of data analysis were data reduction, data display, and conclusion drawing/verification. The findings of this research showed that in syntactically implementing Problem-based learning is the same between the Guru Penggerak and non-penggerak teacher. But individually as teachers there is a distinction between Guru Penggerak and non-penggerak teacher in teaching process. Guru Penggerak tends to give freedom to her students to collaborate, creatively, and express their ideas. While non-penggerak teacher tend to focus more on achieving the learning objective based on lesson plan. In addition, the distinguishes between Guru Penggerak and non-penggerak teacher is their difference perceptions in implementing problem-based learning. Different experiences, teaching method and point of view very visible from the teachers.